Reproducción de la morena, Gymnothorax equatorialis(Pisces: Muraenidae) en Jalisco y Colima, México - Lucano-Ramírez, G. (2008)
A total of 707 Gymnothorax equatorialis were collected monthly in the Jalisco and Colima coast, Mexico, from December 1995 to December 1998 and from August to November 1999, in order to determine their reproduction patterns. Females outnumbered and had longer bodies (mean length 54.7 cm) than males (52.1 cm). The minimum, maximum and mean values of total fecundity were respectively 9 660, 99 992 and 32 029 eggs. The total body length at which 50 percent of individuals have ripe gonads (L50) was 43.7 cm for females and 42.7 cm TL for males. Ovaries had two main types of oocytes: small inmature in cromatin nucleolus phase (85.1 μm) and large mature in secundary vitellogenesis phase (701.6 μm). High numbers of spermatozoa were observed in the seminal tubes of ripe testicles, which presented a lobular development. Based in gonad features and temporal changes in the gonad-somatic index, it is concluded that G. equatorialis has two relatively short reproduction periods (at the middle and at the end of the year)